Bimbingan Penyelesaian Konflik Keluarga Melalui Pendekatan Mediasi - Silawati, Silawati; Aslati, Aslati; S, Mochammad Novendri; Syafiuddin, Fauzan Azima (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This community service activity aims to assist families in resolving conflicts through a mediation approach, a conflict resolution process involving a neutral third party as a facilitator. Family conflicts are common issues arising from differences in opinions, economic pressures, parenting styles, and ineffective communication. These conflicts can affect family harmony and the well-being of its members. The implementation methods include providing education on mediation techniques, training in effective communication, and conducting simulations of conflict resolution in various scenarios. The results show that families participating in the mediation program improved their communication skills, identified the root causes of problems, and reached mutual agreements peacefully. Moreover, mediation helps build healthier communication patterns to prevent future conflicts. This approach has proven effective in fostering harmonious families and serves as a sustainable solution for addressing the dynamics of household.